Neuroprotective Effect of Root Extracts of Berberis Vulgaris (Barberry) on Oxidative Stress on SH-SY5Y Cells - Elham Shahriari Rad; Akram Eidi; Dariush Minai-Tehrani; Shahin Bonakdar; Shahram Shoeibi (Korean Pharmacopuncture Institute, 2022)
Objectives: Oxidative stress plays a key role in chronic and acute brain disorders and neuronal damage associated with Alzheimer disease (AD) and other neurodegeneration symptoms. The neuroprotective effects of berberine and Berberis vulgaris (barberry) root extract against apoptosis induced by hydrogen peroxide (H2O2) in the human SH-SY5Y cell line were studied.Methods : The methanolic extraction of barberry root was performed using a maceration procedure. Oxidative stress was induced in SH-SY5Y cells by H2O2, and an MTT assay was applied to evaluate the neuroprotective effects of berberine and barberry root extract. The cells were pretreated with the half maximal inhibitory concentration (IC50) of each compound (including berberine, barberry root extract, and H2O2), and the anti-apoptotic effects of all components were investigated using RT-PCR.Results : The SH-SY5Y cell viability increased in both groups exposed to 75 and 150 ppm barberry extract compared with that in the H2O2-treated group. The data showed that exposing SH-SY5Y cells to 30 ppm berberine significantly increased the cell viability compared with the H2O2-treated group; treatment with 150 and 300 ppm berberine and H2O2 significantly decreased the SH-SY5Y cell viability and was associated with berberine cytotoxicity. The mRNA levels of Bax decreased significantly under treatment with berberine at 30 ppm compared with the control group. A significant increase in Bcl-2 expression was observed only after treatment with the IC50 of berberine. The expression level of Bcl-2 in cells exposed to both berberine and barberry extracts was also significantly higher than that in cells exposed to H2O2.Conclusion : The outcomes of this study suggest that treatment of SH-SY5Y cells with barberry extract and berberine could suppress apoptosis by regulating the actions of Bcl-2 family members.